Dispersion engineering of MWCNT to control structural and gas transport properties of PU mixed matrix membranes. Issue 6 (December 2020) - Rayekan Iranagh, Farzad; Asghari, Morteza; Parnian, Mohammad Javad
Graphical abstract: Highlights: MWCNTs were functionalized using MDI (4, 4'-Methylene diphenyl diisocyanate). PU/MWCNT (NCO&COOH) MMMs were prepared for CO2 /N2 and CO2 /CH4 separation. Morphological and spectral analysis was carried out. PU membrane containing 0.3 wt.% modified MWCNT (-NCO) has shown superior gas separation properties. Abstract: Carbon dioxide, an important heat-trapping (greenhouse) gas, was eliminated using polyurethane (PU) mixed-matrix membranes (MMMs) prepared with different loadings (0.1, 0.2, 0.3, 0.5, 1.0 wt.%) of functionalized filler (multi-walled carbon nanotubes). The functional groups (–COOH and –NCO) on MWCNTs were used to overcome the aggregation of filler in the membrane matrix. FTIR, XRD, and SEM were used to characterize the functionalized MWCNTs. Furthermore, AFM, FESEM, FTIR, and XRD were used to characterize the morphological and structural properties of membranes. In order to investigate CO2 removal, all the fabricated membranes were evaluated operationally by performing permeation tests of CO2, N2, and CH4 . The prepared MMMs showed an increase in gas permeabilities for all gases with an increase in filler loading from 0.1 wt.% up to 0.3 wt.%, while further increase up to 1.0 wt.% reduced the permeabilities. CO2 removal performance of the MWCNT-filled membranes was improved while the permeability of CO2, ideal selectivity of CO2 /N2, and CO2 /CH4 of MMM with 0.3 wt.% loading of MWCNT-NCO showed an increase about 5%, 51%, and 14%, respectively, in comparison to neat PU membrane. This membrane surpassed Robeson's upper bound.